The Ecology of Foster Care – Resilience and Adaptation into Adulthood. (1st June 2018) - Simmonds, John
Abstract : This paper identifies some of the key debates about the evidence from outcomes for children placed in foster care, the challenging issues in the design of the system, how it operates and what the outcomes for children look like. The paper explores foster care as being based in the evolution of the human species in its capacity to adapt, problem-solve and identify resources through cooperative effort between individuals and social groupings with the family as key. An essential attribute of families and parenting is the ability to form close, meaningful and sustained relationships that provide security, stability and opportunity, including connectedness to the community and the resources that are a part of this. Family forms the basis for the child being able to access personal, social, cultural and economic capital both in the present and into the future. One of the serious issues for foster care is the short-term basis of that commitment and, even when it lasts over the longer term, the care arrangement typically ends as the child reaches adulthood. These issues are explored through the concept of resilience and place foster care within an ecological framework that evolves over time.